Online reviews: A pathway to improve hotel management - Oliveira, Anderson S.; Escola Superior de Gestão, Hotelaria e Turismo, Universidade do Algarve (2020)
The purpose of this study is to verify how online reviews can become a useful tool for the improvement of hotel businesses through an in-depth analysis of selected scientific papers. This systematic literature review analyses refereed journals in English, Spanish and Portuguese, published worldwide between January 2008 and January 2020 and containing the keywords: online reviews, hotel improvement, hotel performance and hotel development, in 11 different databases. After examining 59 relevant papers, a range of approaches showing how online reviews support hotel business development are uncovered. Besides contributing to the existing literature by extending the current research on the use of online reviews, the findings of this study also provide hoteliers with insights on how to take advantage of online reviews. Although several studies approach hotel business development using online reviews, only a few studies have gathered these papers to verify their applications and managerial implications. Thus, this paper aims to fill this research gap.